Effect of lifestyle intervention holistic approach on blood glucose levels, health-related quality of life and medical treatment cost in type 2 diabetes mellitus patients (Acta Scientiarum. Health Sciences, 2021)
Type 2 Diabetes Mellitus (T2DM) is a costly, lifestyle-related disorder, its management is very critical and challenging hence lifestyle intervention may a cornerstone in the reversal and management of T2DM. This study designed to assess the impact of lifestyle intervention holistic (LIH) Model on blood glucose levels (BGL), Health-Related Quality of Life (HRQOL), and medical treatment cost in T2DM patients. This prospective, quasi-experimental study was conducted among 224 T2DM patients in Delhi Diabetes Research Center (DDRC), New Delhi. The study participants were allocated into two groups-Lifestyle Intervention Counseling (LIC) group received lifestyle-based counseling through the LIH model while the Usual-care group received only standard treatment. Study outcomes were assessed at baseline, 3rd, 6th, and 12th month and data were analyzed through SPSS. Study results revealed that LIC participants had decreased in fasting blood glucose 0.26 mg dL-1 (-4.37 to 4.89), blood glucose postprandial -70.16 mg dL-1 (-85.15 to - 55.16), HbA1C -2.82% (-5.26 to - 0.37), medicine cost (p < 0.004), hospitalization cost (p < 0.011), and cost of surgery (p < 0.0005). A significant improvement also observed in HRQOL and adherence towards a holistic model in LIC group. The study concludes that lifestyle-based counseling and its adherence was cost-effective and significantly improves BGL, HRQoL, and medical treatment in T2DM patients.